Understanding the links between agriculture and health: Agriculture, malaria, and water-associated diseases - Mutero, Clifford M.; McCartney, Matthew P.; Boelee, Eline (International Food Policy Research Institute, 2006)
Malaria, schistosomiasis (bilharzia), and Japanese encephalitis are the major vector-borne diseases whose increase or decrease can be attributed to agricultural water development (see table). Others include dengue fever, yellow fever, and filariasis. Young children in poor communities are particularly affected: malaria is among the top five causes of death among under-fives in Sub-Saharan Africa; schistosomiasis among children affects growth, nutritional status, and cognitive development; and encephalitis occurs mainly in young children... Water development projects bring important benefits locally and globally. Yet it is often assumed that irrigation will bring health benefits to all, regardless of their socioeconomic standing within a community. In reality, the economic and social impacts of irrigation are diverse and widespread, and neither costs nor benefits are evenly distributed among community members. In Sub-Saharan Africa, as elsewhere in the world, there is increasing recognition of the need to reduce the negative impacts of agricultural development on ecosystems and peoples’ health. Unless well-targeted interventions are made, the most vulnerable—notably poor children and their mothers—will continue to benefit least from the promise of irrigation and suffer most from the adverse health impacts.